Economic perspectives on employment 2021-2030 (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Long before the pandemic, labour force all over the world was facing the quest of incertitude, which is normal and inherent of the market, but the extent of this quest was shaped by the pace of acceleration of technological progress, which became exponential in the last ten years, from 2010 to 2020. Robotic process automation, work remote, computer science, electronic and communications, mechanical engineering, information technology digitalisation o public administration and so one are ones of the pillars of the future of work. Some authors even stated that without robotic process automation (RPA) included in technological processes, companies will not be able to sustain a competitive level on the market (Madakan et al, 2018). Robots and automation make processes to operate automatically, especially those which are repetitive, emerging a new concept, o robotic workforce.            Prominent empirical studies (Frey and Osborne, 2017 and Acemoglu and Restrepo, 2017) prove that continuous progress in digital and robotic technologies shape a trend towards the demise of work. Prospects of a future where many people will not have jobs due to automation are enhanced by additional publications (Brynjolfsson and McAfee, 2014, Ford, 2015). Automation and the complementary digital technology might come along with unemployment and conversely with inequality, hence the fear of people for what will bring the future. Social and economic policies are to be implemented, such as education for new adaptive skills or, in the worst scenarios, provision of a basic income. Despite of this unsecure perspective, automation processes come in hand with some peculiar qualities: they free people of repetitive tasks, provide availability of 24/7, are convenient and helpful, escape from risky jobs from dangerous situation, bust workflow inefficiencies, shore up productivity. These all are nowadays pillars of further growth, which economic mainstream still supports.Nevertheless, in line with continuous extension of capitalism, work didn’t cease to expand too, occupying workers lives due to new and diversified needs. At the beginnings of capitalism, in the early nineteenth century, the working hour programs were devastating people, from children to elders, forced to work up to exhausting levels, or death sometimes, due to low standard living (Heillbronner, 2005). Until the beginning of twentieth century, thanks to greater productivity and better social and economic policies, the decline of working hours improved the general background of the workforce. Despite of the solid trend improving the life of workers in the expense of working ours, from 1970s the trend has reversed, with a starting point in the United States (Friedman, 2017). Furthermore, in the twentieth century the productivity in United States improved 15 times, and in Europe 18 times, but the working hours has barely halved. Henceforth, a paradox is rising between the general growth efficiency and productivity and the expanding working our program (Spencer, 2018). Historical expectations of high quality of life with abundance and spare time seem to last more to be achieved. More, along with this economic paradox, non-cyclical crisis such as Covid-19 pandemic, decrease more the chances of a restless future for the workforce.This paper offers a critical perspective on the present debate of the future of work, under the provocative context of automation and the unexpected pandemic and its consequences. This debate is targeting economics and social aspects which are colliding in order to identify what is the best template to accept a provocative future with a reality far out our possibility to foreseen. It illustrates, in general, how the idea of online or remote work will face the future of employment, and presents, in particular, what are the short run policies we should to access to get back on track. The paper contributes by setting out some of the main positions in the debate of disruptions brought by pandemic.The Paper is organised as follows. Section two offers some metrological hints on the research and scientific outcomes. Section three discusses issues on historical background on the vision of the reducing of working time. This discussion helps to identify limits in economic thinking and the origin of the ideas in context. Section four draws out the area of automation and its consequences. Section five reflects on the opportunities for changing educational paradigm after pandemic. Section six concludes.